Effects of Acupoint Stimulation with Digital Massager of Oxytocin on the Breast Milk Production of Working Mothers - Anggorowati, Anggorowati; Sutadi, Heriandi; Setyowati, Setyowati; Koestoer, Raldi Artono (Department of Nursing, Faculty of Medicine, Diponegoro University, 2016)
Background: Many breastfeeding mothers find that their milk production decreases or even stops when they return to work due to reduced breastfeeding hormones. Massage can stimulate the oxytocin hormone, and to replace the manual massage, a digital massager of oxytocin (DMO) is developed.Purpose: This study aimed to identify the effects of the DMO on the milk production of the breastfeeding working mothers.Methods: This study employed a quasi-experiment with pretest-posttest control group design. The samples were 93 breastfeeding working mothers in the community with a baby below 6 months. The samples were assigned into the intervention group (n=46) and the control group (n=47). An intervention of using the DMO was given to the mothers in the intervention group by applying the electrodes on the first intercostae of BL-17 and Bl-18 acupoints for 20 minutes in 3 consecutive days. Meanwhile, a standard treatment was given to the control group. Breast milk expression was carried out before and after the use of DMO. The data were analyzed using the Mann-Whitney and the Wilcoxon tests. Results: The results showed that there were differences in the volume of the expressed breast milk before and after the use of the DMO (p=0.00). The mothers in the intervention group increased their milk production on an average of 23 ml when other variables affecting the breastfeeding were controlled.Conclusion: The DMO stimulated and increased the milk production of working mothers. It can also be an alternative to the complementary therapy, especially for the nursing care management of breastfeeding mothers.